An Analysis of Sentence Fragments and Run-On Sentences Found in The Writings Made by The 2nd Year Students of English Department Students of Universitas Negeri Padang - Nabila Alifa Kayoshi; Witri Oktavia (Journal of English Language Teaching, 2022)
This study discusses the sentence fragments and run-on sentences that are made by the students in writing essays. The research design was descriptive. The sample in this study was 31 students of English Department Academic year 2018/2019 of Universitas Negeri Padang. The instrument used was the final exam sheet of essay writing. Based on this research, students made 29 fragments and 38 run-on sentences. This study also showed that most students made comma splices that reach to 37 numbers.